2007
DOI: 10.1039/b618940g
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic fabrication of addressable tethered lipid bilayer arrays and optimization using SPR with silane-derivatized nanoglassy substrates

Abstract: We report the microfluidic fabrication of robust and fluid tethered bilayer arrays within a poly(dimethylsiloxane) (PDMS) chip, and demonstrate its addressability and biosensing by incorporating the GM1 receptor into the bilayer framework for detection of cholera toxin. Rapid optimization of the experimental conditions is achieved by using nanoglassified surfaces in combination with surface plasmon resonance. The ultrathin glassy film on gold mimics glass surfaces employed in microfluidics, allowing real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…A tethered bilayer membrane (tBLM) was formed on the SPR sensor surface and exposed to solutions with different concentrations of diols. tBLMs were prepared using the vesicle fusion method on a hydrophilic surface (Taylor et al, 2007;Chung et al, 2009). First, polyT-BSA was adsorbed on the SPR sensor surface, and then a suspension of polyA-PEG-DPPE-modified SUVs was applied to the surface.…”
Section: Effects Of Diol Solutions On Tblmmentioning
confidence: 99%
See 1 more Smart Citation
“…A tethered bilayer membrane (tBLM) was formed on the SPR sensor surface and exposed to solutions with different concentrations of diols. tBLMs were prepared using the vesicle fusion method on a hydrophilic surface (Taylor et al, 2007;Chung et al, 2009). First, polyT-BSA was adsorbed on the SPR sensor surface, and then a suspension of polyA-PEG-DPPE-modified SUVs was applied to the surface.…”
Section: Effects Of Diol Solutions On Tblmmentioning
confidence: 99%
“…The tBLM was fabricated by the vesicle fusion method using small unilamellar vesicles (SUVs) on a hydrophilic surface (Taylor et al, 2007;Chung et al, 2009). …”
Section: Surface Plasmon Resonance (Spr)mentioning
confidence: 99%
“…Such a construction also allows for the accommodation of proteins [94], incorporated synthetic ion-channels [95] and sugar lectin systems [96]. Taylor et al has reported on SPR detection of cholera toxin using a tethered bilayer [97]. Cornell et al investigated ion channel based sensors with tethered bilayers [98].…”
Section: Tethered Bilayersmentioning
confidence: 99%
“…Such designs are also reminiscent of other on-chip twodimensional assays. 12,[16][17][18] The key to achieving two-dimensional binding assays is to create spatially addressed arrays of bilayers along individual microchannels. There have already been a number of techniques developed to array different bilayer chemistries at each address.…”
Section: Introductionmentioning
confidence: 99%
“…5 In previous work it has been demonstrated that microfluidic devices can be designed for measuring binding affinities in multivalent systems. [5][6][7][8][9][10][11][12][13][14] In our previous setup, ligands were incorporated into supported lipid bilayers (SLBs) coated on the walls and floors of polydimethylsiloxane/glass microchannels. Linear arrays of channels were then monitored by total internal reflection fluorescence microscopy (TIRFM) 15 to obtain equilibrium dissociation constants in one-shot assays.…”
mentioning
confidence: 99%